Pavlovian extinction of fear with the original conditional stimulus, a generalization stimulus, or multiple generalization stimuli. (August 2018) - Zbozinek, Tomislav D.; Craske, Michelle G.
Abstract: Exposure therapy for anxiety disorders is derived from Pavlovian extinction learning. With the aim of optimizing exposure therapy, the present study evaluated the effects of multiple extinction stimuli on inhibitory learning. In a differential fear conditioning procedure, participants were randomized to one of three extinction conditions: Extinction_CS+ received nine presentations of the original conditional stimulus (CS+); Extinction_Singular received nine presentations of a generalization stimulus (GS; stimulus similar to the CS+); and Extinction_Variety received one presentation each of nine GSs. One week later, participants returned for extinction test to the CS+, CS-, a GS from Extinction_Variety (Variable_GS), the GS from Extinction_Singular (Single_GS), and a novel GS (Novel_GS). Results showed that Extinction_CS+ exhibited less fear of the CS+ than Extinction_Singular (two dependent measures) and Extinction_Variety (three dependent measures). Additionally, Extinction_Singular had more fear of the Variable_GS than Extinction_Variety (two dependent measures) and Extinction_CS+ (one dependent measure). The results suggest that conducting extinction to the CS+ lessens conditional fear of the CS + more than extinction with GSs. Additionally, extinction with a variety of GSs lessens fear of those GSs more than repeated extinction with one GS. Results are discussed with relevance to exposure therapy for anxiety disorders. Highlights: Participants underwent fear conditioning to a conditional stimulus (CS+). Extinction was conducted with the CS+, a generalization stimulus (GS), or nine GSs. Extinction to the CS + reduced CS + fear more than extinction to a GS or nine GSs. Extinction to nine GSs reduced fear to those GSs more than extinction to one GS. Results discussed with relevance for exposure therapy for anxiety disorders.